PENGARUH SISTEM AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP PEMBERIAN KREDIT OLEH PT BANK OCBC NISP TBK KOTA BATAM - Syahril Effendi; Baru Harahap (LPPM Universitas Putera Batam, 2020)
This study aims to prove that the existence of partial and simultaneous influence of variables Accounting System (X1) and Internal Control (X2) of the variable Lending (Y) at PT Bank OCBC NISP Tbk Batam. The analysis used in this study is Regression Analysis which has the aim to determine the regression coefficients besarknya which will show the influence of the independent variables on the dependent variable. The results of the t test showed that variables Accounting System (X1) significantly affects Lending (Y) with Tcount (7,469) Ttable (1.65521) with significant = 0.000 <0.05 and Internal Control (X2) significantly affects Lending (Y) with tcount (6,339) Ttable (1.65521) with significant = 0.000 <0.05. F Test results showed that the Accounting System (X1) and Internal Control (X2) simultaneously influence on Lending (Y) with Fcount (659.4509)> Ftable (3.06) and significant = 0.000 <0.05. Rated R Square of 0.899, showing the extent of the role or contribution of variables Accounting and Internal Control Systems is able to explain the variable Lending by 89.9%, while 10.1% are influenced by factors that are not included in this study.